2019
DOI: 10.1016/j.kint.2019.07.024
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative, individual-level analysis compared longitudinal outcomes across the International Network of Chronic Kidney Disease (iNETCKD) cohorts

Abstract: Rates of chronic kidney disease (CKD) progression, end stage kidney disease (ESKD), all-cause mortality, and cardiovascular (CVD) events among individuals with CKD vary widely across countries. Well-characterized demographic, comorbidity, and laboratory markers captured for prospective cohorts may explain, in part, such differences. To investigate whether core characteristics of individuals with CKD explain differences in rates of outcomes, we conducted an individual-level analysis of eight studies that are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
36
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 36 publications
(45 reference statements)
8
36
2
Order By: Relevance
“…( independently associated with KRT incidence. (3,4,10,13,25) It also showed that in more developed countries, the private for-profit share of hemodialysis facilities was also associated with higher KRT incidence, This study and ours raise the issue of overtreatment related to early-start dialysis in countries with extremely high KRT incidence. In France, eGFR level at dialysis start explained a substantial part of the variations in KRT incidence between regions.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…( independently associated with KRT incidence. (3,4,10,13,25) It also showed that in more developed countries, the private for-profit share of hemodialysis facilities was also associated with higher KRT incidence, This study and ours raise the issue of overtreatment related to early-start dialysis in countries with extremely high KRT incidence. In France, eGFR level at dialysis start explained a substantial part of the variations in KRT incidence between regions.…”
Section: Discussionsupporting
confidence: 60%
“…(12, 13) These variations in CKD progression, however, persisted despite adjustment for baseline eGFR, age, sex, albuminuria, comorbidities, and use of renin-angiotensin system inhibitors. The international network of CKD cohorts (iNET-CKD) hasalso observed different baseline profiles and highly heterogeneous risks of CKD progression, KRT incidence, and mortality among individuals with CKD participating in eight cohort studies around the globe (12,13). This study also observed that adjustment for several patient characteristics and laboratory markers did not substantially attenuate the differences in outcomes.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Since this systematic review was conducted, two further articles have been published reporting the prevalence of the KDIGO 2012 albuminuria categories from the UK, Germany, France and USA [41,42] (Table S6). The cohorts included patients with CKD, with a higher proportion of moderately and severely increased albuminuria compared with the general population cohorts included in this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of research and improved understanding of CKD and its causes, consequences, and cures, there are several international collaborative research efforts facilitated by the ISN with its partners. ISN-ACT (Advancing Clinical Trials) aims to connect the global kidney clinical trial community to increase capacity and quality of trials answering important questions; iNET CKD (International Network of CKD Cohorts) has established a collaborative research network with individuallevel data and bio-samples to examine variation in outcomes and biological parameters around the world and to leverage that information to inform clinical trials as needed [13][14][15]. The Hydration for Kidney Health initiative (ISN-H4KH), a partnership between Danone and ISN, has established research projects and supported investigators who are interested in improving the understanding of the role of hydration in specific environments and specific kidney disease populations.…”
Section: Introductionmentioning
confidence: 99%